Verification of procedure for calculating the working processes of lubrication free low-speed long-stroke piston high-pressure stages - S. S. Busarov; A. V. Nedovenchany; D. I. Bukhanets; K. V. Scherban (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The results of the conducted experimental studies of operating processes of the air-speed slow-speed stage of the pre-price compressor verifying the calculation method for the described stage size taking into account the effect of intensive cooling and without intensive cooling with increasing pressure from atmospheric pressure to 10 MPa in one stage, which until now has not been accomplished by any pressing from the researchers